MERANCANG LEMBAGA KEUANGAN MIKRO SYARIAH YANG TEPAT PADA DESA KAREHKEL, KECAMATAN LEUWILIANG, KABUPATEN BOGOR - Anwar, Miftakhul; Mursyidah, Azizah; Anjas, Muhamad (SAHID DEVELOPMENT JOURNAL : Jurnal Pengabdian Kepada Masyarakat Perbankan Syariah, 2024)
This research aims to increase prosperity with Islamic values in the community and MSMEs in Karehkel Village through empowerment in the region by designing a sharia microfinance institution in Karehkel village. The subject of this study is the residents of Karehkel Village, especially MSMEs, and underprivileged residents. The results of this study show that sharia microfinance institutions in Karehkel Village are increasing and have a positive effect on Karehkel Village. And this research shows that the community needs a sharia microfinance institution in Karehkel Village.